2023
DOI: 10.9734/jammr/2023/v35i155064
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated Oil as a Desensitizing Protocol in External Dental Bleaching: A Clinical, Randomized and Double-Blind Study

Iara Fretta Wiggers,
Márcio José Mendonça,
Rafael Vanolli
et al.

Abstract: Aims: This research aimed to evaluate the action of ozonized oil associated with an obliterating desensitizing agent in reducing post-dental bleaching sensitivity. Study Design:  This was a randomized, prospective, double-blind, split-mouth study, in which the patient and evaluator were blinded to the distribution of the groups. Place and Duration of Study: The study was conducted at the Dentistry Clinics of the Local University from June to December 2021. Methodology: Forty patients were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Ozonized oil was selected due to its advantage of allowing prolonged contact of ozone with the dental surface, as its half-life is significantly longer [15]. In a randomized clinical trial, Wiggers et al [11] found a significant reduction in postbleaching sensitivity using ozonized sunflower oil associated with glutaraldehyde. Possibly, the authors found a more pronounced desensitizing effect in the group treated with ozonized sunflower oil in combination with glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozonized oil was selected due to its advantage of allowing prolonged contact of ozone with the dental surface, as its half-life is significantly longer [15]. In a randomized clinical trial, Wiggers et al [11] found a significant reduction in postbleaching sensitivity using ozonized sunflower oil associated with glutaraldehyde. Possibly, the authors found a more pronounced desensitizing effect in the group treated with ozonized sunflower oil in combination with glutaraldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…The effect size used of 0.50, error type 1(α) of 0.05, and power of analysis (error β) of 0.90 resulted in a total of 26 volunteers per group. For convenience, due to the possible dropout of patients, 30 patients were selected per group [11,12]. The sample calculation was performed in the GPower program, version 3.1.9.2 -University of Düsseldorf.…”
Section: Sample Size Calculationmentioning
confidence: 99%